Apoptotic Index of Amniotic Membrane Cells in Preterm Labor with Premature Rupture of Membrane (PPROM) was Higher than Preterm Labor without Premature Rupture of Membrane - Giri Chandra (Journal of Global Pharma Technology, 2020)
Introduction: Premature rupture of the membrane in preterm pregnancy is a condition that can cause increased maternal and perinatal morbidity and mortality. The study aims to compare the apoptotic index of amniotic membrane cells in preterm labor with premature rupture of membrane (PPROM) and without premature rupture of membrane. Method: This is a cross sectional study conducted at the Department of Obstetrics and Gynecology, Sanglah Hospital Bali. The Amniotic membranes were taken from the placenta after delivery then apoptotic index was measured by TUNEL examination. Result: The study included each 20 women from both groups. There was no significant difference of maternal age, gestational age, and BMI between groups (p>0,05). Chi-square analysis showed there was an association between the apoptotic index and preterm labor with PROM (p = 0.001). Subsequent analysis resulted in prevalence ratio of 19.0 (95% CI = 2.81 - 128.6). Conclusion: This study concluded that the apoptotic index of amniotic membrane cells in PPROM was higher than preterm labor without premature rupture of membrane. Keywords: Apoptotic index, Preterm Premature Rupture of Membrane, PPROM.